Aldehyde aromatic compound cross-linked polyethyleneimine as well as preparation method and application thereof
By crosslinking polyethyleneimine with aldehyde aromatic compounds to form aldehyde aromatic compounds, the problems of unstable polyethyleneimine in solution and low adsorption capacity are solved, and the effect of efficient adsorption of gold ions and platinum ions is achieved.
Patent Information
- Application Number
- CN202411964715.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
Polyethyleneimine is unstable in solution as an adsorbent and has a low adsorption capacity to metal ions.
By crosslinking the polyethyleneimine with an aldehyde aromatic compound, the aldehyde aromatic compound crosslinks the polyethyleneimine, thereby improving its stability in solution and adsorption ability to metal ions.
Aldehyde aromatic compound crosslinked polyethyleneimine has high adsorption capacity and excellent selectivity, and can effectively adsorb gold and platinum ions, and maintain good performance in multiple cycles.
Smart Images

Figure BDA0005221063610000011 
Figure BDA0005221063610000031 
Figure BDA0005221063610000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to an aldehyde aromatic compound cross-linked polyethylene imine and a preparation method and application thereof. Background Art
[0002] Precious metals are widely used because of their good physical and chemical properties, but their reserves are relatively small, so people often recover precious metals from secondary resources. Common methods for recovering precious metals include membrane separation, electrochemical method, ion exchange method and adsorption method. Among them, the adsorption method is simple to operate and can efficiently remove low-concentration precious metals, especially organic polymer material adsorbents, which are widely used due to their low cost, simple preparation and operation, and clear mechanism analysis.
[0003] Polyethyleneimine (PEI) is a high molecular polymer rich in N atoms and has many side chain amine groups, which can provide a large number of adsorption sites for metal attachment. It has the advantages of fast adsorption rate, low boiling point and easy desorption and degradation. However, polyethyleneimine is unstable as an adsorbent in solution and has a low adsorption capacity for metal ions. Summary of the invention
[0004] The purpose of the present invention is to provide an aldehyde aromatic compound cross-linked polyethylene imine and a preparation method and application thereof. The aldehyde aromatic compound cross-linked polyethylene imine provided by the present invention has good stability and high adsorption capacity.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides an aldehyde aromatic compound cross-linked polyethyleneimine, the structural unit of which is shown in formula A:
[0007]
[0008] In formula A, R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently -H or -OH; and n is 1 to 140.
[0009] Preferably, the aldehyde aromatic compound cross-linked polyethyleneimine includes one of trialdehyde phloroglucinol cross-linked polyethyleneimine, 2-hydroxy-1,3,5-benzenetricarboxaldehyde cross-linked polyethyleneimine, trimesic acid cross-linked polyethyleneimine and 2,4-dihydroxy-1,3,5-trisic acid cross-linked polyethyleneimine.
[0010] The present invention also provides a method for preparing the aldehyde aromatic compound cross-linked polyethyleneimine described in the above scheme, comprising the following steps:
[0011] Polyethyleneimine, an aldehyde aromatic compound and an organic solvent are mixed to carry out a cross-linking reaction to obtain the aldehyde aromatic compound cross-linked polyethyleneimine.
[0012] Preferably, the weight average molecular weight of the polyethyleneimine is 600-70,000.
[0013] Preferably, the aldehyde aromatic compound includes one or more of trialdehyde phloroglucinol, 2,4-dihydroxy-1,3,5-benzenetricarboxaldehyde, 2-hydroxy-1,3,5-benzenetricarboxaldehyde and trimesic acid.
[0014] Preferably, the molar ratio of the polyethyleneimine to the aldehyde aromatic compound is 1-5:1-4.
[0015] Preferably, the temperature of the cross-linking reaction is 0 to 100° C., and the heat preservation cross-linking time is 1 to 5000 min.
[0016] The present invention also provides the use of the aldehyde aromatic compound cross-linked polyethyleneimine described in the above scheme or the aldehyde aromatic compound cross-linked polyethyleneimine obtained by the preparation method described in the above scheme in the field of metal ion adsorption.
[0017] Preferably, the application of the aldehyde aromatic compound cross-linked polyethyleneimine in the field of metal ion adsorption comprises the following steps: mixing the aldehyde aromatic compound cross-linked polyethyleneimine, a pH regulator and wastewater containing precious metal ions, conducting an adsorption reaction, and then performing solid-liquid separation to obtain a saturated adsorbent and treated wastewater; and the saturated adsorbent is desorbed and reused.
[0018] Preferably, the mass volume ratio of the aldehyde aromatic compound cross-linked polyethyleneimine to the wastewater containing precious metal ions is (0.001-1) g: (1-4000) mL.
[0019] The present invention provides an aldehyde aromatic compound cross-linked polyethyleneimine. The aldehyde aromatic compound cross-linked polyethyleneimine provided by the present invention has a mesoporous structure, and adsorbs gold ions and platinum ions onto the surface and inside the pores of the material through electrostatic attraction, chelation coordination and oxidation-reduction mechanisms, thereby improving the adsorption capacity of metal ions, especially gold ions and platinum ions, with high adsorption capacity and excellent selectivity for gold ions and platinum ions; at the same time, through the cross-linking of polyethyleneimine and the aldehyde aromatic compound, it can have better stability.
[0020] The present invention utilizes the amino groups in polyethyleneimine to combine with aldehyde aromatic compounds containing different numbers of hydroxyl groups, thereby improving the adsorption capacity of the polyethyleneimine cross-linked with the aldehyde aromatic compounds; in addition, polyethyleneimine has a high degree of cationicity in water, and can neutralize and adsorb anions or chelate noble metal ions, thereby improving the adsorption of noble metals; in addition, the amino groups in the polyethyleneimine structure can undergo a cross-linking reaction with the aldehyde aromatic compounds, and a C=N double bond is introduced into the polyethyleneimine, thereby improving the adsorption performance of noble metal ions.
[0021] The present invention also provides a method for preparing the cross-linked polyethyleneimine with aldehyde aromatic compounds described in the above scheme. In the present invention, the amino groups in polyethyleneimine and the aldehyde groups in the aldehyde aromatic compounds are cross-linked to produce a Schiff base synthesis reaction to obtain the cross-linked polyethyleneimine with aldehyde aromatic compounds. Polyethyleneimine contains a large number of amino groups and has high chemical reactivity. It tends to be protonated under acidic conditions and provides adsorption sites for precious metals, but it is unstable in solution. In the present invention, the polyethyleneimine is made stable in solution by cross-linking with the aldehyde aromatic compounds.
[0022] The present invention also provides the use of the cross-linked polyethyleneimine of the aldehyde aromatic compound described in the above scheme or the cross-linked polyethyleneimine of the aldehyde aromatic compound obtained by the preparation method described in the above scheme in the field of metal ion adsorption. The cross-linked polyethyleneimine of the aldehyde aromatic compound provided by the present invention can be used to treat wastewater containing precious metal ions. The results of the embodiments show that the adsorption amount of gold ions by the cross-linked polyethyleneimine of the aldehyde aromatic compound provided by the present invention at 25°C is 3082.72 mg / g, and the adsorption amount of platinum ions is 608.28 mg / g, and the selectivity for gold ions and platinum ions is excellent, and it can selectively adsorb and recover gold ions and platinum ions from 11 kinds of ions. DETAILED DESCRIPTION
[0023] The present invention provides an aldehyde aromatic compound cross-linked polyethyleneimine, the structural unit of which is shown in formula A:
[0024]
[0025] In formula A, R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently -H or -OH; and n is 1 to 140.
[0026] In the present invention, n in Formula A is preferably 5-100, more preferably 8-80, and further preferably 12-40.
[0027] In the present invention, the aldehyde aromatic compound cross-linked polyethyleneimine preferably includes one of trialdehyde phloroglucinol cross-linked polyethyleneimine (structural unit such as formula B, the value range of n is the same as formula A), 2-hydroxy-1,3,5-benzenetricarboxaldehyde cross-linked polyethyleneimine (structural unit such as formula D, the value range of n is the same as formula A), trimesic acid cross-linked polyethyleneimine (structural unit such as formula E, the value range of n is the same as formula A) and 2,4-dihydroxy-1,3,5-trisic acid cross-linked polyethyleneimine (structural unit such as formula C, the value range of n is the same as formula A).
[0028]
[0029]
[0030] In the present invention, the aldehyde aromatic compound cross-linked polyethyleneimine has the characteristics of large adsorption capacity, low boiling point, low toxicity, stable properties, acid and alkali resistance, sufficient adsorption saturation sites, excellent adsorption effect, and can be recycled many times. The reason is that noble metal ions are generally in anionic state in solution, and the materials modified by easily protonated amino polyethyleneimine have higher adsorption capacity and better ion selectivity for noble metals.
[0031] The aldehyde aromatic compound cross-linked polyethyleneimine provided by the present invention has a mesoporous structure, the material properties are stable, acid and alkali resistant, and the adsorption saturation sites are sufficient. Gold ions and platinum ions are adsorbed onto the surface and pores of the material through electrostatic attraction, chelate coordination, oxidation-reduction and other mechanisms, and can be used for selectively adsorbing gold and platinum ions in wastewater, with an excellent adsorption effect.
[0032] The present invention also provides a method for preparing the aldehyde aromatic compound cross-linked polyethyleneimine described in the above scheme, comprising the following steps:
[0033] Polyethyleneimine, an aldehyde aromatic compound and an organic solvent are mixed to carry out a cross-linking reaction to obtain the aldehyde aromatic compound cross-linked polyethyleneimine.
[0034] In the present invention, unless otherwise specified, the reagents used in the present invention are all conventional commercial products in the art.
[0035] The present invention mixes polyethyleneimine, aldehyde aromatic compound and organic solvent (referred to as the first mixing). In the present invention, the weight average molecular weight of the polyethyleneimine is preferably 600 to 70,000, specifically 600, 800, 1,000, 3,000, 5,000, 8,000, 10,000, 30,000, 50,000 or 70,000. The present invention uses polyethyleneimine with the above molecular weight, which is beneficial to improving the adsorption capacity of the aldehyde aromatic compound cross-linked polyethyleneimine for noble metal ions.
[0036] In the present invention, the aldehyde aromatic compound preferably includes one or more of trialdehyde phloroglucinol, 2,4-dihydroxy-1,3,5-pyromellitic aldehyde, 2-hydroxy-1,3,5-benzenetricarboxaldehyde and pyromellitic aldehyde, and more preferably trialdehyde phloroglucinol. The present invention uses the aldehyde aromatic compound as a raw material and introduces a C=N double bond into polyethyleneimine, which can improve the adsorption capacity of precious metal ions.
[0037] In the present invention, the molar ratio of the polyethyleneimine to the aldehyde aromatic compound is preferably 1 to 5:1 to 4, specifically 1:1, 1:2, 1:3, 1:4, 2:1, 2:3, 3:1, 3:2, 3:4, 4:1, 4:3, 5:1, 5:2, 5:3 or 5:4. The present invention controls the amount of polyethyleneimine and the aldehyde aromatic compound within the above range, which is beneficial to improving the adsorption performance of the aldehyde aromatic compound cross-linked polyethyleneimine.
[0038] In the present invention, the organic solvent preferably includes one or both of ethanol and N,N-dimethylformamide (DMF), and more preferably N,N-dimethylformamide.
[0039] The present invention has no special requirements for the amount of the organic solvent, as long as the polyethyleneimine can fully cross-link. In a specific embodiment of the present invention, the mass volume ratio of the polyethyleneimine to the organic solvent is preferably (0.1-0.2) g: (0.3-0.45) mL, specifically 0.1 g: 0.35 mL, 0.1 g: 0.4 mL, 0.2 g: 0.35 mL or 0.2 g: 0.4 mL.
[0040] The present invention has no special requirements for the first mixing method, and the polyethyleneimine, the aldehyde aromatic compound and the organic solvent can be evenly mixed. In a specific embodiment of the present invention, the first mixing is preferably: polyethyleneimine and an organic solvent are mixed to obtain a polyethyleneimine solution, and then the aldehyde aromatic compound is added dropwise to the polyethyleneimine solution.
[0041] After the raw materials are mixed, the present invention conducts a cross-linking reaction on the obtained raw material mixture to obtain the aldehyde aromatic compound cross-linked polyethylene imine. In the present invention, the temperature of the cross-linking reaction is preferably 0 to 100°C, specifically 10°C, 20°C, 35°C, 45°C, 55°C, 70°C or 90°C, and the heat preservation cross-linking time is preferably 1 to 5000min, specifically 10min, 100min, 400min, 720min, 1000min, 3000min or 5000min. The present invention controls the temperature and time of the cross-linking reaction within the above range, which is conducive to sufficient reaction.
[0042] In the present invention, after the cross-linking reaction, the process preferably further comprises: centrifuging, washing and drying the reaction solution in sequence. The present invention can remove unreacted impurities and solvents in the system through centrifugation, washing and drying.
[0043] In the present invention, the washing is preferably performed sequentially by alcohol washing and water washing; the alcohol is preferably ethanol; the ethanol is preferably ethanol with a volume fraction of 95% or anhydrous ethanol; the water used for the water washing is preferably ultrapure water.
[0044] In the present invention, the drying is preferably freeze drying, the freeze drying temperature is preferably -40 to -50°C, specifically -45°C, the heat preservation and drying time is preferably 5 to 24h, specifically 10h or 16h.
[0045] The preparation method provided by the invention has green and environmentally friendly solvents, simple steps and fast synthesis rate.
[0046] The present invention also provides the use of the aldehyde aromatic compound cross-linked polyethyleneimine described in the above scheme or the aldehyde aromatic compound cross-linked polyethyleneimine obtained by the preparation method described in the above scheme in the field of metal ion adsorption.
[0047] The aldehyde aromatic compound cross-linked polyethyleneimine provided by the invention can be used for treating wastewater containing noble metal ions.
[0048] In the present invention, the application of treating wastewater containing precious metal ions preferably includes the following steps: mixing aldehyde aromatic compound cross-linked polyethyleneimine, pH regulator and wastewater containing precious metal ions (obtaining a mixed solution), subjecting the mixture to an adsorption reaction and then subjecting the mixture to solid-liquid separation to obtain a saturated adsorbent and treated wastewater; and desorbing the saturated adsorbent and reusing it.
[0049] In the present invention, the concentration of gold ions in the wastewater containing precious metal ions is preferably not higher than 1000 mg / L, and can be specifically 10 mg / L, 50 mg / L, 100 mg / L, 300 mg / L, 500 mg / L, 700 mg / L or 1000 mg / L; the concentration of platinum ions is preferably not higher than 1000 mg / L, and can be specifically 5 mg / L, 10 mg / L, 50 mg / L, 100 mg / L, 300 mg / L, 500 mg / L, 700 mg / L or 1000 mg / L.
[0050] In the present invention, the mass volume ratio of the aldehyde aromatic compound cross-linked polyethyleneimine to the wastewater containing precious metal ions is preferably (0.001-1) g:(1-4000) mL, specifically 0.001 g:1 mL, 0.001 g:10 mL, 0.001 g:100 mL, 0.001 g:1000 mL, 0.001 g:2000 mL, 0.001 g:4000 mL, 0.01 g:1 mL, 0.01 g:10 mL, 0.001 g:1000 mL, 0.001 g:2000 mL, 0.001 g:4000 mL, 0.01 g:1 mL, 0.01 g:10 mL, 0 .01g:100mL, 0.01g:1000mL, 0.01g:2000mL, 0.01g:4000mL, 0.1g:1mL, 0.1g:10mL, 0.1g:100mL, 0.1g:1000mL, 0.1g:2000mL, 0.1g:4000mL, 1g:1mL, 1g:10mL, 1g:100mL, 1g:1000mL, 1g:2000mL or 1g:4000mL.
[0051] In the present invention, the pH adjuster is preferably hydrochloric acid; the amount of the pH adjuster added is preferably based on adjusting the pH value of the mixed solution to 1 to 13, specifically 3, 5, 7 or 9. The present invention controls the pH value of the mixed solution within the above range, which can improve the adsorption capacity of the aldehyde aromatic compound cross-linked polyethyleneimine for precious metal ions.
[0052] In the present invention, the temperature of the adsorption reaction is preferably room temperature, specifically 25°C, and the adsorption time is preferably no more than 3000 min, specifically 5 min, 10 min, 50 min, 100 min, 300 min, 500 min, 720 min, 1000 min, 1500 min, 2000 min or 2500 min. The present invention can achieve adsorption equilibrium at the above temperature and time, and fully adsorb the precious metal ions in the wastewater.
[0053] In the present invention, the adsorption reaction is preferably carried out under oscillation conditions; the oscillating device is preferably an oscillator. The present invention can improve mass transfer through oscillation, making the adsorption more complete.
[0054] The present invention has no special limitation on the solid-liquid separation method; the present invention preferably uses conventional methods to remove metal ions from saturated adsorbents. The aldehyde aromatic compound cross-linked polyethyleneimine prepared by the present invention has good stability, so it can be reused after desorption.
[0055] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0056] Example 1
[0057] In this embodiment, trialdehyde phloroglucinol cross-linked polyethyleneimine was prepared. The preparation method steps are as follows: 0.5 g of polyethyleneimine with a molecular weight of 10,000 was dissolved in 5 mL of N,N-dimethylformamide (DMF) under ultrasonic action to obtain a polyethyleneimine solution, 80 mg of trialdehyde phloroglucinol was dissolved in 5 ml of DMF under ultrasonic action to obtain a trialdehyde phloroglucinol solution, the two solutions were mixed, reacted at 25° C. for 15 h, and then centrifuged at 6000 r / min for 10 min in a high-speed centrifuge, the lower layer of solid precipitate was removed, washed with 95% ethanol and ultrapure water respectively to remove incompletely reacted impurities, and then freeze-dried overnight to obtain an orange solid, i.e., trialdehyde phloroglucinol cross-linked polyethyleneimine.
[0058] Example 2
[0059] In this embodiment, trialdehyde phloroglucinol cross-linked polyethyleneimine was prepared. The preparation method steps are as follows: 0.375 g of polyethyleneimine with a molecular weight of 10,000 was dissolved in 5 mL of DMF under ultrasonication to obtain a polyethyleneimine solution, 42 mg of trialdehyde phloroglucinol was dissolved in DMF under ultrasonication to obtain a trialdehyde phloroglucinol solution, the two solutions were mixed, reacted at 25° C. for 15 h, and then centrifuged at 6000 r / min for 10 min in a high-speed centrifuge, the lower layer of solid precipitate was removed, washed with 95% ethanol and ultrapure water respectively to remove impurities that were not completely reacted, and then freeze-dried overnight to obtain an orange solid, i.e., trialdehyde phloroglucinol cross-linked polyethyleneimine.
[0060] Example 3
[0061] In this embodiment, trialdehyde phloroglucinol cross-linked polyethyleneimine was prepared. The preparation method steps are as follows: 0.075 g of polyethyleneimine with a molecular weight of 10,000 was dissolved in 5 mL of DMF under ultrasonic action to obtain a polyethyleneimine solution, 42 mg of trialdehyde phloroglucinol was dissolved in DMF under ultrasonic action to obtain a trialdehyde phloroglucinol solution, the two solutions were mixed, reacted at 25° C. for 720 min, and then centrifuged at 6000 r / min for 10 min in a high-speed centrifuge, the lower layer of solid precipitate was removed, washed with 95% ethanol and ultrapure water respectively to remove incompletely reacted impurities, and then freeze-dried overnight to obtain a gray-black solid, i.e., trialdehyde phloroglucinol cross-linked polyethyleneimine.
[0062] Example 4
[0063] In this embodiment, trialdehyde phloroglucinol cross-linked polyethyleneimine was prepared. The preparation method steps are as follows: 0.024 g of polyethyleneimine with a molecular weight of 10,000 was dissolved in 5 mL of DMF under ultrasonication to obtain a polyethyleneimine solution, 52.2 mg of trialdehyde phloroglucinol was dissolved in DMF under ultrasonication to obtain a trialdehyde phloroglucinol solution, the two solutions were mixed, reacted at 25° C. for 720 min, and then centrifuged at 6000 r / min in a high-speed centrifuge for 10 min, the lower layer of solid precipitate was removed, washed with 95% ethanol and ultrapure water respectively to remove incompletely reacted impurities, and then freeze-dried overnight to obtain a red solid, i.e., trialdehyde phloroglucinol cross-linked polyethyleneimine.
[0064] Example 5
[0065] In this embodiment, trialdehyde phloroglucinol cross-linked polyethyleneimine was prepared. The preparation method steps are as follows: 0.09 g of polyethyleneimine with a molecular weight of 10,000 was dissolved in 5 mL of DMF under ultrasonic action to obtain a polyethyleneimine solution, 105 mg of trialdehyde phloroglucinol was dissolved in DMF under ultrasonic action to obtain a trialdehyde phloroglucinol solution, the two solutions were mixed, reacted at 25° C. for 720 min, and then centrifuged at 6000 r / min in a high-speed centrifuge for 10 min, the lower layer of solid precipitate was removed, and washed with 95% ethanol and ultrapure water respectively to remove impurities that were not completely reacted, and then freeze-dried overnight to obtain trialdehyde phloroglucinol cross-linked polyethyleneimine.
[0066] Example 6
[0067] In this embodiment, 2-hydroxy-1,3,5-benzenetricarboxaldehyde cross-linked polyethyleneimine is prepared. The preparation method has the following steps: 0.0475 g of polyethyleneimine with a molecular weight of 10,000 is dissolved in 5 mL of DMF under ultrasonication to obtain a polyethyleneimine solution; 67.79 mg of 2-hydroxy-1,3,5-benzenetricarboxaldehyde is dissolved in DMF under ultrasonication to obtain a 2-hydroxy-1,3,5-benzenetricarboxaldehyde solution; the two solutions are mixed, reacted at 25° C. for 720 min, and then centrifuged at 6000 r / min in a high-speed centrifuge for 10 min, the lower layer of solid precipitate is removed, and washed with 95% ethanol and ultrapure water respectively to remove impurities that have not been completely reacted, and then freeze-dried overnight to obtain 2-hydroxy-1,3,5-benzenetricarboxaldehyde cross-linked polyethyleneimine.
[0068] Example 7
[0069] In this embodiment, trimesic acid cross-linked polyethyleneimine is prepared. The preparation method steps are as follows: 0.0475 g of polyethyleneimine with a molecular weight of 10,000 is dissolved in 5 mL of DMF under ultrasonic action to obtain a polyethyleneimine solution, 61.61 mg of trimesic acid is dissolved in DMF under ultrasonic action to obtain a trimesic acid solution, the two solutions are mixed, reacted at 25° C. for 720 min, and then centrifuged at 6000 r / min in a high-speed centrifuge for 10 min, the lower layer of solid precipitate is removed, and washed with 95% ethanol and ultrapure water respectively to remove impurities that have not been completely reacted, and then freeze-dried overnight to obtain trimesic acid cross-linked polyethyleneimine.
[0070] Example 8
[0071] In this embodiment, 2,4-dihydroxy-1,3,5-triscarboxaldehyde cross-linked polyethyleneimine is prepared. The preparation method has the following steps: 0.1425 g of polyethyleneimine with a molecular weight of 10,000 is dissolved in 5 mL of DMF under ultrasonic action to obtain a polyethyleneimine solution, 73.7 mg of 2,4-dihydroxy-1,3,5-triscarboxaldehyde is dissolved in DMF under ultrasonic action to obtain a 2,4-dihydroxy-1,3,5-triscarboxaldehyde solution, the two solutions are mixed, reacted at 25° C. for 720 min, and then centrifuged at 6000 r / min in a high-speed centrifuge for 10 min, the lower layer of solid precipitate is removed, and washed with 95% ethanol and ultrapure water respectively to remove impurities that have not been completely reacted, and then freeze-dried overnight to obtain 2,4-dihydroxy-1,3,5-triscarboxaldehyde cross-linked polyethyleneimine.
[0072] Application Example 1
[0073] 550 mg / L Au(III) and 100 mg / L Pt(IV) aqueous solutions were prepared respectively, 13 centrifuge tubes were taken, 20 mL of Au(III) aqueous solution was added to each centrifuge tube, and then the pH value of the Au(III) aqueous solution in each centrifuge tube was adjusted to make the pH value of the Au(III) aqueous solution 1, 2, 3, 4, 5, 6, 8, 9, 10, 11, 12 and 13. Another 13 centrifuge tubes were taken, 20 mL of Pt(IV) aqueous solution was added to each centrifuge tube, and then the pH value of the Pt(IV) aqueous solution in each centrifuge tube was adjusted to make the pH value of the Pt(IV) aqueous solution 1, 2, 3, 4, 5, 6, 8, 9, 10, 11, 12 and 13 respectively.
[0074] 5 mg of the trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 was added to each of the above centrifuge tubes, and the mixture was placed in a constant temperature water bath oscillator at 25°C and oscillated for 48 hours. After the adsorption was completed, the upper metal ion solution was taken and diluted to a concentration of 0-15 mg / L, so that it could be detected by atomic absorption. The residual concentration of gold was tested by atomic absorption spectrophotometer (AA-6680), and the residual concentration of platinum was tested by inductively coupled plasma mass spectrometry (7850). The corresponding adsorption rate and adsorption capacity were calculated, and the calculation formulas used were as follows:
[0075]
[0076] In the formula, subscripts t and e represent time t and equilibrium state respectively, subscript 0 represents the initial value; q t represents the adsorption capacity at time t, q e represents the adsorption capacity at the equilibrium time; R% represents the adsorption rate. The calculation results are shown in Tables 1 and 2.
[0077] Table 1 Effect of pH value on Au(III) adsorption rate
[0078] pH Adsorption rate R% Adsorption capacity (mg / g) 1 88.50 1385.46 2 88.83 1390.53 3 93.49 1463.47 4 95.71 1498.24 5 95.80 1499.75 6 94.39 1477.68 8 62.02 970.94 9 51.13 800.45 10 25.71 402.44 11 12.87 201.46 12 7.72 120.83 13 3.84 60.04
[0079] Table 2 Effect of pH value on Pt(IV) adsorption rate
[0080] pH Adsorption rate R% Adsorption capacity (mg / g) 1 44.43 437.58 2 48.40 476.68 3 48.20 474.69 4 48.00 472.73 5 37.90 373.25 6 38.88 382.91 7 27.89 274.64 8 34.49 339.63 9 24.30 239.29 10 23.95 235.83 11 7.41 72.96 12 1.96 19.31 13 1.27 12.50
[0081] It can be seen from Tables 1 and 2 that as the pH value decreases, the adsorption effects of Au(III) and Pt(IV) ions become better and better; and for Au(III), when the pH value is 5, the maximum adsorption capacity reaches 1499.75 mg / g, and the adsorption rate is 95.80%; for Pt(IV), when the pH value is 2, the maximum adsorption capacity reaches 476.68 mg / g, and the adsorption rate is 48.40%.
[0082] Application Example 2
[0083] Prepare 10 mg / L Au (III) aqueous solution and 10 mg / L Pt (IV) aqueous solution respectively, add hydrochloric acid to adjust the pH value of gold to 5 and the pH value of platinum to 2. Take 20 mL of each solution and add them to 2 50 mL centrifuge tubes respectively, then add 5 mg of trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 to the above 2 centrifuge tubes respectively, and place them in a constant temperature water bath oscillator at 25° C. for 0 to 720 min. After the adsorption is completed, take the upper metal ion solution at 1 min, 3 min, 5 min, 7 min, 10 min, 15 min, 30 min, 60 min, 120 min, 240 min, 360 min, and 720 min respectively, dilute the solution to 0 to 15 mg / L, test the residual concentration of gold with an atomic absorption spectrophotometer (AA-6680), test the residual concentration of platinum with an inductively coupled plasma mass spectrometer (7850), and calculate the corresponding adsorption rate and adsorption capacity. For Au(III), equilibrium was reached in 60 min, the adsorption rate at equilibrium was 90%, and complete adsorption required 720 min. For Pt(IV), equilibrium was reached in 5 min, the adsorption rate at equilibrium was 91.88%, and complete adsorption required 720 min.
[0084] Application Example 3
[0085] Prepare 550 mg / L Au(III) aqueous solution and 100 mg / L Pt(IV) aqueous solution respectively, add hydrochloric acid to adjust the pH value of gold to 5 and the pH value of platinum to 2. Take 20 mL of each solution and add them to two 50 mL centrifuge tubes respectively, then add 5 mg of trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 to the two centrifuge tubes respectively, and place them in a constant temperature water bath shaker at 25°C for 0 to 2880 min. After the adsorption was completed, the upper metal ion solution was taken at 1min, 5min, 10min, 30min, 45min, 60min, 120min, 240min, 360min, 480min, 720min, 1440min, 2160min, 2880min, and 4320min, respectively, and the solution was diluted to 0-15mg / L, and the residual concentration of gold was tested by atomic absorption spectrophotometer (AA-6680), and the residual concentration of platinum was tested by inductively coupled plasma mass spectrometry (7850), and the corresponding adsorption rate and adsorption capacity were calculated. For Au (III), equilibrium was reached at 1440min, and its adsorption rate at equilibrium was 84.09%. For Pt (IV), equilibrium was reached at 360min, and its adsorption rate at equilibrium was 98.37%.
[0086] Application Example 4
[0087] Au(III) aqueous solutions with a pH value of 5 and a concentration of 10 mg / L, 50 mg / L, 70 mg / L, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 550 mg / L, 600 mg / L, 650 mg / L, 700 mg / L, 800 mg / L, 900 mg / L, 1000 mg / L, 1100 mg / L, 1200 mg / L and 1300 mg / L were prepared respectively, and 20 mL of each Au(III) solution was transferred into 18 centrifuge tubes.
[0088] 5 mg of trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 was added to the above centrifuge tubes, sealed, and placed in a constant temperature water bath oscillator at 25°C for 72 hours. After the adsorption was completed, the solution was diluted to 0-15 mg / L, and the residual concentration was tested with an atomic absorption spectrophotometer (AA-6680), and the corresponding adsorption rate was calculated. The results are shown in Table 3.
[0089] Table 3 Effect of solution concentration on adsorption rate
[0090]
[0091] According to Table 3, it can be seen that as the initial concentration increases, the adsorption rate decreases, and the maximum adsorption capacity of the adsorbent for Au (III) is 2974.87 mg / g.
[0092] Application Example 5
[0093] A mixed solution was prepared according to the ion concentration ratio of Au (III): Pt (IV): miscellaneous ions = 10 mg / L: 10 mg / L: 100 mg / L, wherein the miscellaneous ions include 9 kinds of Pb (II), Zn (II), K (I), Na (I), Ni (II), Co (II), Cu (II), Fe (III), Al (III), etc., provided in the form of nitrates, and the molar ratio of the 9 kinds of ions is 1: 1: 1: 1: 1: 1: 1: 1: 1. 20 mL of the mixed solution was placed in a 50 mL centrifuge tube, 5 mg of the trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 was added, and after sealing, it was placed in a constant temperature water bath oscillator at 25 ° C for 2 hours. After the adsorption was completed, the solution was diluted to 0-15 mg / L, and the residual concentration was tested by atomic absorption spectrophotometer (AA-6680) and inductively coupled plasma mass spectrometry (ICP-MS), and the corresponding adsorption rate and adsorption capacity were calculated. The results show that the adsorption rate of Au(III) is 99.997% after 120 min, and the adsorption rate of Pt(IV) is 95.268% after 120 min. The adsorption rates of impurity ions are: Pb(II) is 7.377%, Zn(II) is 0.578%, K(I) is 4.276%, Na(I) is 5.042%, Ni(II) is 0.624%, Co(II) is 0.5%, Cu(II) is 5.186%, Fe(III) is 0%, and Al(III) is 0%. This shows that the trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 has excellent selective adsorption performance for gold ions and platinum ions.
[0094] Application Example 6
[0095] Prepare 550 mg / L Au(III) aqueous solution and 100 mg / L Pt(IV) aqueous solution, take 13 centrifuge tubes, add 20 mL of Au(III) aqueous solution to each centrifuge tube, and then adjust the pH value of Au(III) aqueous solution in each centrifuge tube to make the pH value of Au(III) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13. Take another 13 centrifuge tubes, add 20 mL of Pt(IV) aqueous solution to each centrifuge tube, and then adjust the pH value of Pt(IV) aqueous solution in each centrifuge tube to make the pH value of Pt(IV) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13.
[0096] 5 mg of trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 2 was added to each of the above centrifuge tubes, and the mixture was placed in a constant temperature water bath oscillator at 25°C for 48 hours. After adsorption, the upper metal ion solution was taken, and the solution was diluted to 0-15 mg / L. The residual concentration of gold was tested by atomic absorption spectrophotometer (AA-6680), and the residual concentration of platinum was tested by inductively coupled plasma mass spectrometry (7850), and the corresponding adsorption rate and adsorption capacity were calculated. The results show that as the pH value decreases, the adsorption effect on Au (III) ions and Pt (IV) ions is getting better and better.
[0097] Application Example 7
[0098] Prepare 550 mg / L Au(III) aqueous solution and 100 mg / L Pt(IV) aqueous solution, take 13 centrifuge tubes, add 20 mL of Au(III) aqueous solution to each centrifuge tube, and then adjust the pH value of Au(III) aqueous solution in each centrifuge tube to make the pH value of Au(III) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13. Take another 13 centrifuge tubes, add 20 mL of Pt(IV) aqueous solution to each centrifuge tube, and then adjust the pH value of Pt(IV) aqueous solution in each centrifuge tube to make the pH value of Pt(IV) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13.
[0099] 5 mg of the trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 3 was added to each of the above centrifuge tubes, and the mixture was placed in a constant temperature water bath oscillator at 25°C for 48 hours. After the adsorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15 mg / L. The residual concentration of gold was tested by an atomic absorption spectrophotometer (AA-6680), and the residual concentration of platinum was tested by an inductively coupled plasma mass spectrometer (7850), and the corresponding adsorption rate and adsorption capacity were calculated. The results showed that as the pH value decreased, the adsorption effect on Au (III) and Pt (IV) ions became better and better.
[0100] Application Example 8
[0101] 550 mg / L Au(III) and 100 mg / L Pt(IV) aqueous solutions were prepared respectively, 13 centrifuge tubes were taken, 20 mL of Au(III) aqueous solution was added to each centrifuge tube, and then the pH value of the Au(III) aqueous solution in each centrifuge tube was adjusted to make the pH value of the Au(III) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13. Another 13 centrifuge tubes were taken, 20 mL of Pt(IV) aqueous solution was added to each centrifuge tube, and then the pH value of the Pt(IV) aqueous solution in each centrifuge tube was adjusted to make the pH value of the Pt(IV) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13 respectively.
[0102] 5 mg of the trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 4 was added to each of the above centrifuge tubes, and the mixture was placed in a constant temperature water bath oscillator at 25°C for 48 hours. After the adsorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15 mg / L. The residual concentration of gold was tested by an atomic absorption spectrophotometer (AA-6680), and the residual concentration of platinum was tested by an inductively coupled plasma mass spectrometer (7850), and the corresponding adsorption rate and adsorption capacity were calculated. The results showed that as the pH value decreased, the adsorption effect on Au (III) and Pt (IV) ions became better and better.
[0103] Application Example 9
[0104] 550 mg / L Au(III) and 100 mg / L Pt(IV) aqueous solutions were prepared respectively, 13 centrifuge tubes were taken, 20 mL of Au(III) aqueous solution was added to each centrifuge tube, and then the pH value of the Au(III) aqueous solution in each centrifuge tube was adjusted to make the pH value of the Au(III) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13. Another 13 centrifuge tubes were taken, 20 mL of Pt(IV) aqueous solution was added to each centrifuge tube, and then the pH value of the Pt(IV) aqueous solution in each centrifuge tube was adjusted to make the pH value of the Pt(IV) aqueous solution 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13 respectively.
[0105] 5 mg of the trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 5 was added to each of the above centrifuge tubes, and the mixture was placed in a constant temperature water bath oscillator at 25°C for 48 hours. After the adsorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15 mg / L. The residual concentration of gold was tested by an atomic absorption spectrophotometer (AA-6680), and the residual concentration of platinum was tested by an inductively coupled plasma mass spectrometer (7850), and the corresponding adsorption rate and adsorption capacity were calculated. The results showed that as the pH value decreased, the adsorption effect on Au (III) and Pt (IV) ions became better and better.
[0106] Application Example 10
[0107] 20 mL of Au (III) aqueous solution with a concentration of 991.18 mg / L was added to 5 centrifuge tubes respectively, and hydrochloric acid was added to adjust the pH value to 5 respectively, 5 mg of trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 was added to each of the above centrifuge tubes, and then the above 5 centrifuge tubes were placed in a constant temperature water bath oscillator at 5°C, 15°C, 25°C, and 45°C for 72 hours; 1 group was selected to conduct the experiment under the same conditions. After the adsorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15 mg / L, and the residual concentration of gold was tested by an atomic absorption spectrophotometer (AA-6680), and the residual concentration of platinum was tested by an inductively coupled plasma mass spectrometer (7850), and the corresponding adsorption rate and adsorption capacity were calculated. The results are shown in Table 4.
[0108] Table 4 Effect of temperature on Au(III) adsorption rate and adsorption capacity
[0109]
[0110] It can be seen from Table 4 that with the increase of adsorption temperature, the adsorption rate and adsorption capacity gradually increase. At 45 °C, the adsorbent has a better adsorption rate and adsorption capacity for gold ions.
[0111] 20 mL of 336.585 mg / L Pt (IV) aqueous solution was added to 5 centrifuge tubes, and hydrochloric acid was added to adjust the pH value to 2. 5 mg of trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 was added to each of the above centrifuge tubes, and then the above 5 centrifuge tubes were placed in a constant temperature water bath oscillator at 5°C, 15°C, 25°C, 35°C, and 45°C for 72 hours; 1 group was selected to conduct the experiment under the same conditions. After the adsorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15 mg / L, and the residual concentration was tested by inductively coupled plasma mass spectrometry (7850), and the corresponding adsorption rate and adsorption capacity were calculated. The results are shown in Table 5.
[0112] Table 5 Effect of temperature on Pt(IV) adsorption rate and adsorption capacity
[0113]
[0114] It can be seen from Table 5 that with the increase of adsorption temperature, the adsorption rate and adsorption capacity gradually increase. At 45 °C, the adsorbent has a better adsorption rate and adsorption capacity for platinum ions.
[0115] Application Example 11
[0116] 150mL of Au (III) aqueous solution with a concentration of about 113mg / L was added to the centrifuge tube, and hydrochloric acid was added to adjust the pH value to 5. 0.075g of trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 was added to the above centrifuge tube, and then the above centrifuge tube was placed in a 25°C constant temperature water bath oscillator for 12h. After the adsorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15mg / L, and the residual concentration was tested with an atomic absorption spectrophotometer (AA-6680), and the corresponding adsorption rate was calculated; the adsorbed metal ion solution was desorbed, and 150mL of desorption solution (thiourea: hydrochloric acid = 1mol / L: 1mol / L) was added for desorption for 30min. After the desorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15mg / L, and the residual concentration was tested with an atomic absorption spectrophotometer (AA-6680), and the corresponding desorption rate was calculated. The results are shown in Table 6.
[0117] Table 6 Repeatability test results of trialdehyde phloroglucinol cross-linked polyethyleneimine for Au(III)
[0118]
[0119] According to Table 6, it can be seen that the adsorbent dropped from 100% to 76% after seven cycles, and the solution concentration returned to its original state after rapid desorption for 30 minutes, indicating that trialdehyde phloroglucinol cross-linked polyethyleneimine has good reuse performance for Au(III). The rapid decline in the reuse of Au(III) may be due to the redox reaction of Au(III). During desorption, the mass loss of trialdehyde phloroglucinol cross-linked polyethyleneimine is large and it is also difficult to desorb.
[0120] 150 mL of a 118.096 mg / L Pt (IV) aqueous solution was added to the centrifuge tube, and hydrochloric acid was added to adjust the pH value to 2. 0.075 g of the trialdehyde phloroglucinol cross-linked polyethyleneimine prepared in Example 1 was added to the centrifuge tube, and then the centrifuge tube was placed in a 25°C constant temperature water bath oscillator for 12 hours. After the adsorption was completed, the upper metal ion solution was taken, and the solution was diluted to 0-15 mg / L, and the residual concentration was tested with an atomic absorption spectrophotometer (AA-6680), and the corresponding adsorption rate was calculated as shown in Table 7.
[0121] Table 7 Repeatability test results of trialdehyde phloroglucinol cross-linked polyethyleneimine for Pt(IV)
[0122] frequency Total concentration before adsorption (mg / L) Total concentration after adsorption (mg / L) Adsorption rate R% first 118.096 0.09472 99.92 Second time 118.096 1.87602 98.41 The third time 118.096 1.42807 98.79 Fourth 118.096 2.92806 97.52 Fifth 118.096 2.98272 97.47 Sixth 118.096 3.0006 97.46 Seventh 118.096 6.2192 94.73 Eighth 118.096 8.787 92.46 Ninth 118.096 10.3414 91.24 The tenth time 118.096 39.1107 66.88
[0123] According to Table 7, after 10 cycles, the adsorption rate of trialdehyde phloroglucinol cross-linked polyethyleneimine dropped from 99.92% to 66.88%, indicating that trialdehyde phloroglucinol cross-linked polyethyleneimine has good reusability for Pt(IV).
[0124] Application Example 12
[0125] Prepare 250.245 mg / L Au(III) aqueous solution, take 20 mL and add it to a centrifuge tube, add 5 mg of 2-hydroxy-1,3,5-benzenetricarboxaldehyde cross-linked polyethyleneimine prepared in Example 6 to the above centrifuge tube, and then place the above centrifuge tube in a 25°C constant temperature water bath oscillator for 12 hours. After the adsorption is completed, take the upper metal ion solution, dilute the solution to 0-15 mg / L, test the residual concentration with an atomic absorption spectrophotometer (AA-6680), and calculate the corresponding adsorption rate. The results show that the adsorption rate of 250.245 mg / L Au(III) aqueous solution is 51.35%, the adsorption amount is 513.972 mg / g, and the solution is yellow.
[0126] Application Example 13
[0127] Prepare 7.1064mg / L and 250.245mg / L Au(III) aqueous solutions, take 20mL and add them to two centrifuge tubes, add 5mg of 2,4-dihydroxy-1,3,5-triphenylamine cross-linked polyethyleneimine prepared in Example 8 to the above centrifuge tubes, and then place the above centrifuge tubes in a 25℃ constant temperature water bath oscillator for 12h. After the adsorption is completed, take the upper metal ion solution, dilute the solution to 0-15mg / L, test the residual concentration with an atomic absorption spectrophotometer (AA-6680), and calculate the corresponding adsorption rate. The results show that the adsorption rate of 7.1064mg / L Au(III) aqueous solution is 78.86%, the adsorption amount is 22.4156mg / g, and the solution is slightly purple; the adsorption rate of 250.245mg / L Au(III) aqueous solution is 80.77%, the adsorption amount is 808.5mg / g, and the solution is yellow.
[0128] It can be seen from the above embodiments that the aldehyde aromatic compound cross-linked polyethyleneimine provided by the present invention can effectively adsorb gold ions and platinum ions, has a high adsorption capacity, has good selectivity for gold ions and platinum ions, has a fast adsorption rate, good stability, and can be reused.
[0129] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An aldehyde aromatic compound cross-linked polyethyleneimine, characterized in that: The structural unit is shown in formula A: In formula A, R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently -H or -OH; and n is 1 to 140.
2. The aldehyde aromatic compound cross-linked polyethyleneimine according to claim 1, characterized in that: The aldehyde aromatic compound cross-linked polyethyleneimine includes one of trialdehyde phloroglucinol cross-linked polyethyleneimine, 2-hydroxy-1,3,5-benzenetricarboxaldehyde cross-linked polyethyleneimine, trimesic acid cross-linked polyethyleneimine and 2,4-dihydroxy-1,3,5-trisic acid cross-linked polyethyleneimine.
3. The method for preparing the cross-linked polyethyleneimine of aldehyde aromatic compound according to any one of claims 1 to 2, characterized in that: The following steps are involved: Polyethyleneimine, an aldehyde aromatic compound and an organic solvent are mixed to carry out a cross-linking reaction to obtain the aldehyde aromatic compound cross-linked polyethyleneimine.
4. The preparation method according to claim 3, characterized in that: The weight average molecular weight of the polyethyleneimine is 600-70,000.
5. The preparation method according to claim 3, characterized in that: The aldehyde aromatic compound includes one or more of trialdehyde phloroglucinol, 2,4-dihydroxy-1,3,5-pyromellitic trimesicaldehyde, 2-hydroxy-1,3,5-benzenetricarboxaldehyde and pyromellitic trimesicaldehyde.
6. The preparation method according to claim 3 or 5, characterized in that: The molar ratio of the polyethyleneimine to the aldehyde aromatic compound is 1-5:1-4.
7. The preparation method according to claim 3 or 4, characterized in that: The temperature of the cross-linking reaction is 0-100° C., and the heat preservation cross-linking time is 1-5000 min.
8. Use of the cross-linked polyethyleneimine of the aldehyde aromatic compound according to any one of claims 1 to 2 or the cross-linked polyethyleneimine of the aldehyde aromatic compound obtained by the preparation method according to any one of claims 3 to 7 in the field of metal ion adsorption.
9. The use according to claim 8, characterized in that: The following steps are involved: Aldehyde aromatic compound cross-linked polyethyleneimine, pH regulator and wastewater containing precious metal ions are mixed for adsorption reaction and then solid-liquid separation is performed to obtain a saturated adsorbent and treated wastewater; the saturated adsorbent is reused after desorption.
10. The use according to claim 9, characterized in that: The mass volume ratio of the aldehyde aromatic compound cross-linked polyethyleneimine to the wastewater containing precious metal ions is (0.001-1) g: (1-4000) mL.
Citation Information
Cited By
Preparation method and application of betaine modified polyethyleneimine
CN121517700A